2006
DOI: 10.1111/j.1475-2743.2006.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the variability of UK sugar beet yields under climate change and husbandry adaptations

Abstract: In the future, UK summers are likely to be warmer and drier. Modelling differential water redistribution and uptake, we assessed the impact of future drier climates on sugar beet yields. Weather was generated for 1961-1990 (BASE) and predictions based on low- and high-emission scenarios (LO, HI) described in the most recent global climate simulations by the Hadley Centre, UK. Distributions and variability of relative soil moisture deficit (rSMD) and yield gap (drought-related yield loss, YG(dr) = 1-actual yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Higher temperatures and a shorter LGP alone would reduce potential yield but similar to potato, sugar beet benefits substantially from the CO 2 fertilization effect (illustrated by the no-CO 2 scenarios). The simulated positive trends for sugar beet yield are in agreement with simulated impacts in the UK (Richter et al 2006).…”
Section: Sugar Beetsupporting
confidence: 78%
“…Higher temperatures and a shorter LGP alone would reduce potential yield but similar to potato, sugar beet benefits substantially from the CO 2 fertilization effect (illustrated by the no-CO 2 scenarios). The simulated positive trends for sugar beet yield are in agreement with simulated impacts in the UK (Richter et al 2006).…”
Section: Sugar Beetsupporting
confidence: 78%
“…Analysis of bi‐weekly soil moisture measurements showed a statistically significant difference between the two groups. These results confirm that the experimental design had a direct impact on the growing environment, which was then reflected in the wet yield data: the mean mass of the control category was 359.5 g; the mean in the future group was 318.5 g. This is consistent with Richter et al (), who modelled the response of UK sugar beet under climate change and found that water will be a major stress factor in future and relative soil moisture will be reduced under a high greenhouse gas emission scenario.…”
Section: Discussionmentioning
confidence: 97%
“…They found that water will be a major stress factor in the future and that relative soil moisture will be reduced under high greenhouse gas emission scenarios. The analysis presented here extends the work of Richter et al () by using daily precipitation projections from a climate model ensemble to inform a controlled watering experiment in a greenhouse, which is relevant to potential future rainfall conditions in east England under medium and high greenhouse gas emission scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, biomass from forest is the main source for bioenergy, but for transport biofuel most renewable sources come from first‐generation crops used for food and feed like rapeseed, sugar, and starch crops . Productivity for such crops like sugarbeet has been assessed at the national and European scale . Second‐generation biofuel feedstocks from herbaceous and woody crops currently focus on Miscanthus in the UK and in Europe, and short rotation coppice (SRC) .…”
Section: Biofuel Cropland Modelingmentioning
confidence: 99%